Effect of Plant Growth Regulators on Growth, Yield and Quality of Chilli (Capsicum annuum L.) at Rampur, Chitwan - Chaudhary, BR; Sharma, MD; Shakya, SM; Gautam, DM (Journal of the Institute of Agriculture and Animal Science, 2006)
The present investigation was carried out in the plain areas of Chitwan to determine the promising plant growth regulators (PGR) promoting growth and yield of chilli cultivars Jwala and Suryamukhi during winter-summer season of 2003/2004. Suryamukhi ranked superior to Jwala for most of the yield attributing characters, whereas Jwala was better in vegetative characters than Suryamukhi. Among PGRs, 2,4-D at 2 ppm was better for fruit set, number of fruits per plant, fruit length, number of seeds per fruit, seed weight per fruits, 1000 seed weight and fruit yield where as NAA at 40 ppm gave the highest leaf area index (LAI). PGRs were ineffective in promoting flowering and fruiting during winter season. GA3 at 10 ppm exhibited maximum amount of ascorbic acid content. The treatments, 2 ppm 2,4-D, 5 ppm triacontanol, 40 ppm NAA and 10 ppm GA3 produced 28.75%, 25.70%, 13.61% and 2.30% higher fruit yield over control, respectively. The highest net profit and B:C ratio were recorded in case of 2 ppm 2,4-D. The use of GA3 as foliar spray was not economical. Key words: 2,4-D, NAA, triacontanol, GA3, leaf area index, net profit, B:C ratio J. Inst. Agric. Anim. Sci. 27:65-68 (2006)